(untitled) (Journal of Universal Science Research, 2023)
Shadow economy is a complex phenomenon that involves economic activities operating outside the purview of government regulations, taxation, and control. The presence of the shadow economy poses both challenges and opportunities for society. It harms society by reducing government revenue through tax evasion and diverting resources towards the detection and concealment of informal labor. This article explores the different definitions and implications of the shadow economy. It discusses how a cashless economy can help manage price levels and reduce illicit trade and tax evasion.